Boys Write About Boys: Androcentrism in Children's Reading Experience and Its Emergence in Children's Own Writing. Issue 6 (6th July 2021) - Hsiao, Yaling; Banerji, Nilanjana; Nation, Kate
Abstract : Gender bias exists in our language environment. We investigated personal name usage in two large corpora of language written for and by U.K. children aged 5–13. Study 1 found an overrepresentation of male names in children's books, largely attributable to male authors. In stories written by over 100, 000 children, Study 2 found an overall male bias that interacted with age. Younger children wrote more about their own gender. With age, girls became more balanced yet boys continued to show a strong male bias. Our findings demonstrate a male‐centered bias in both children's books and their own writing. We consider the power of written language to both shape and be shaped by cultural stereotypes via systematic biases in gender associations.